GENERAL ASPECTS REGARDING THE EVOLUTION OF THE MANAGEMENT OF THE FORMS OF COOPERATION AND ASSOCIATION IN ROMANIA COMPARED TO THOSE IN THE EUROPEAN UNION - Popescu, Alin (Annales Universitatis Apulensis Series Oeconomica, 2017)
The article brings to the fore some general aspects regarding the evolution of the management of the forms of cooperation and association in Romania compared to those in the European Union. In Romania today it is necessary to make agricultural farms as profitable as possible, with markets which should be competitive and efficient in accessing various financial funds. The purpose of the article is to present the necessity of encouraging the association and cooperation of small farmers, as well as the problems that cause the Romanian producers association process to stagnate.